2021
DOI: 10.3126/hijost.v5i01.42129
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasitic Infections and Associated Risk Factors Among School-going Children of Age 1-5 years in Dharan, Eastern Nepal

Abstract: Intestinal parasitic infections have been a major public health burden of developing countries, especially in children. Higher prevalence has been reported among school children, mostly in rural areas of Nepal where water, toilets, hygiene, and sanitation facilities are insufficient. This cross-sectional study was carried out from April to September 2019 to determine the prevalence of intestinal parasitic infections among school-going children1-5 years of Dharan, Nepal, and to assess the associated risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…The result of the current studies showed that children taking drugs for the intestine parasite in the last six months had less odds of stunting compared to children had no taking drugs for the intestine parasite in the last six months it is consistent with previous studies reported in Eastern Nepal, Ethiopia and Tanzania, [ 11 , 23 , 24 ] it could be due to the routine vitamin A supplementation, protective or curative deforming combined with Integrated Management of Neonatal and Childhood Illness may benefit to decrease the problem of childhood stunting. The current study showed that the odds of stunting was higher among twin pregnancies mother compared with that of singleton pregnancies mother which is in line with study conducted in South Africa [ 25 ], East Africa [ 26 ] and Italy [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…The result of the current studies showed that children taking drugs for the intestine parasite in the last six months had less odds of stunting compared to children had no taking drugs for the intestine parasite in the last six months it is consistent with previous studies reported in Eastern Nepal, Ethiopia and Tanzania, [ 11 , 23 , 24 ] it could be due to the routine vitamin A supplementation, protective or curative deforming combined with Integrated Management of Neonatal and Childhood Illness may benefit to decrease the problem of childhood stunting. The current study showed that the odds of stunting was higher among twin pregnancies mother compared with that of singleton pregnancies mother which is in line with study conducted in South Africa [ 25 ], East Africa [ 26 ] and Italy [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…The result of the current studies showed that children taking drugs for the intestine parasite in the last six months had less odds of stunting compared to children had no taking drugs for the intestine parasite in the last six months it is consistent with previous studies reported in Eastern Nepal, Ethiopia and Tanzania, [11,23,24] it could be due to the routine vitamin A supplementation, protective or curative deforming combined with Integrated Management of…”
Section: Discussionsupporting
confidence: 91%
“…Mainly, G. lamblia was seen higher in male gender and younger age group had more prevalence of infection than the older ones 39 . Yet, few studies reported similar risk of IPIs between male and female 40 . In this study, majority of female reported healthier behavioral and lifestyle characteristics (i.e., less consumption of pork) compared to male participants ( p < 0.05), which may explain such discrepancy in IPIs infection by gender.…”
Section: Discussionmentioning
confidence: 53%
“…39 Yet, few studies reported similar risk of IPIs between male and female. 40 In this study, majority of female reported healthier behavioral and lifestyle characteristics (i.e., less consumption of pork) compared to male participants ( p < 0.05), which may explain such discrepancy in IPIs infection by gender. Another study carried out in rural Nepal showed contrasting results to our study where younger girls were more infected (55.2%) than boys (44.8%).…”
Section: Discussionmentioning
confidence: 61%